If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 324(1 + -1x) = 36 (1 * 324 + -1x * 324) = 36 (324 + -324x) = 36 Solving 324 + -324x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-324' to each side of the equation. 324 + -324 + -324x = 36 + -324 Combine like terms: 324 + -324 = 0 0 + -324x = 36 + -324 -324x = 36 + -324 Combine like terms: 36 + -324 = -288 -324x = -288 Divide each side by '-324'. x = 0.8888888889 Simplifying x = 0.8888888889
| 18.8=2*3.14*r | | -7a^2b+2ab^2= | | 210=4*9*5+2*5*H | | x^2-11x+82=0 | | 2x+3=5x-5/3 | | y+x=r | | 2(x+9)=3(x-3) | | 78=2x-12 | | 9=y+c | | 20+b=a | | 4/3=x+2/8 | | 5w+6=16w-3w+54 | | 9y-14=6y-2 | | -3w+11=-8w+51 | | y=7x^2-4x | | 7x-5y-10=0 | | 24=-11y-8+3y | | 60*0.2= | | 3w-4=-16 | | -32=w/5-7 | | -v+131=180 | | 31=-u+184 | | 205=96-y | | -25=4u+3 | | 82-(4-6)2= | | 25n^8-49n^7-2n^6=0 | | -3+w=-4 | | -6=u-4 | | 5(2x-9)+3x=4x-18 | | 13=0.5((4x-10)+(3x+8)) | | 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x |